Synthesis of Some 5-Substituted-1,2,4-triazole-3-thiones, Containing Thiourea, Arylidenamino and Morpholin-4-yl methyl Fragments - Koparir, Metin; Koparir, Pelin; Cansiz, Ahmet; Mursit Temuz, Mehmet (Asian Journal of Chemistry, 2010)
In this study, first 4-amino-5-(pyridine-4yl)-4H-1,2,4-triazole-3-thione (1) and 4-amino-5-(2- hydroxyphenyl)-4H-1,2,4-triazole-3-thione (2) were synthesized. In the second step (1) and (2) compounds undergo reaction with aryl isothiocyanates in dry C6H6 to give corresponding Nsubstituted thiourea derivatives (3a-d and 4a-d). In addition, in the another reaction (1) and (2) compounds were reacted with some aromatic aldehyde in anhydrous ethanol to give corresponding arylidenamino compounds (5a-d and 6a-d). In the third step, aminomethylation derivatives (7a-d and 8a-d) were obtained by the Mannich reactions of arylidenamino compounds (5a-d and 6a-d), with formaldehyde/morpholine in ethanol. The structures of all the synthesized compounds were confirmed by elemental analyses, FT-IR, 1H and 13C NMR spectra.